2023
DOI: 10.1136/bmjopen-2022-067840
|View full text |Cite
|
Sign up to set email alerts
|

Screening tools for predicting mortality of adults with suspected sepsis: an international sepsis cohort validation study

Abstract: ObjectivesWe evaluated the performance of commonly used sepsis screening tools across prospective sepsis cohorts in the USA, Cambodia and Ghana.DesignProspective cohort studies.Setting and participantsFrom 2014 to 2021, participants with two or more SIRS (Systemic Inflammatory Response Syndrome) criteria and suspected infection were enrolled in emergency departments and medical wards at hospitals in Cambodia and Ghana and hospitalised participants with suspected infection were enrolled in the USA. Cox proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Patients with respiratory failure may be at particularly risk in hospitals without respiratory support including high flow nasal cannula and mechanical ventilation or access to supplemental oxygen upon discharge. Elevated UVA scores, qSOFA scores, and point-of-care lactate were each associated with an increased risk of death consistent with prior studies in LMICs 7,16,24 . Prior research that demonstrated the additive prognostic value of serum lactate in Uganda, Malawi, and Southeast Asia 3,25,26 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Patients with respiratory failure may be at particularly risk in hospitals without respiratory support including high flow nasal cannula and mechanical ventilation or access to supplemental oxygen upon discharge. Elevated UVA scores, qSOFA scores, and point-of-care lactate were each associated with an increased risk of death consistent with prior studies in LMICs 7,16,24 . Prior research that demonstrated the additive prognostic value of serum lactate in Uganda, Malawi, and Southeast Asia 3,25,26 .…”
Section: Discussionsupporting
confidence: 85%
“…Persons 18 years of age and older presenting with suspected infection and ≥ 2 modified systemic inflammatory response syndrome (SIRS) criteria (temperature < 36°C or > 38°C, heart rate ≥ 90 beats per minute, or respiratory rate ≥ 20 breaths per minute) were enrolled at Fort Portal Regional Referral Hospital (FPRRH) in Fort Portal, Uganda. SIRS was incorporated in sepsis cohorts 7 prior to Sepsis 3 criteria 8 and maintained for consistency. Adult patients 18 years of age and older presenting at the outpatient department, emergency department, or medical wards were evaluated for enrollment from October 2017 to August 2022.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed patient samples from sepsis studies completed in Cambodia (20) and Ghana (19) to measure changes in UCH-L1 or GFAP as a result of bacterial infection. This study population was comprised of 53 severely ill, hospitalized patients who presented with at least two systemic inflammatory response syndrome criteria and a suspected infection.…”
Section: Resultsmentioning
confidence: 99%
“…A normal score is ≥ 26, whereas impairment falls into mild (18)(19)(20)(21)(22)(23)(24)(25), moderate (10)(11)(12)(13)(14)(15)(16)(17), and severe (< 10) categories. Previous sepsis studies completed in Ghana (19) provided serum samples collected prospectively from hospitalized cases of sepsis at study enrollment (day 0) and day 28 after enrollment. MoCA-B scores were determined for individuals at study enrollment, upon discharge, on day 28, and 6 and 12 months after discharge, when feasible.…”
Section: Study Population 3: Bacterial Sepsis With Cognitive Assessmentmentioning
confidence: 99%
See 1 more Smart Citation